2002
DOI: 10.1046/j.1460-9592.2002.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of cleft type with incidence of perioperative respiratory complications in infants with cleft lip and palate

Abstract: Clinicians should consider postponing primary plastic surgery for cleft lip and palate in infants with a suspected presence of a common cold. Our results also suggest that the presence of a wide cleft is a risk factor for causing perioperative respiratory complications in infants with cleft lip and palate. We believe that a careful preoperative assessment of common cold symptoms in these infants can decrease the incidence of perioperative respiratory complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 5 publications
2
62
0
Order By: Relevance
“…A study from Tokyo observed a 4% incidence of respiratory complications in cleft surgeries in infants < 6 months. 1 That study however did not take into account tube-related factors and intubation difficulties. Filles 7 demonstrated an 8.6% incidence of respiratory complications in their series of 174 infants.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…A study from Tokyo observed a 4% incidence of respiratory complications in cleft surgeries in infants < 6 months. 1 That study however did not take into account tube-related factors and intubation difficulties. Filles 7 demonstrated an 8.6% incidence of respiratory complications in their series of 174 infants.…”
Section: Discussionmentioning
confidence: 98%
“…1 We therefore ensured that all our patients were symptomfree, normothermic with normal white cell count and no recent history of cold symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 There are a few studies on perioperative complications in cleft lip and palate surgery, but these are largely from developed nations. 3,[5][6][7][8][9] In most developed countries, cleft lip and palate care has evolved into organised cleft teams based in regional or supraregional centres. 1 The situation is different in most developing nations, where lack of trained medical personnel still hinders a high-quality dedicated team approach to delivery of care to orofacial cleft patients.…”
Section: Introductionmentioning
confidence: 99%